NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides with high diastereoselectivity: a short route to (-)-cytoxazone and droxidopa - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letter, 2007)
The NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides was achieved using lithium bromide as the bromine source under acidic conditions at rt to afford the corresponding chiral alpha-bromo-beta-hydroxy carboxamides. Excellent yields (77-90%) and diastereoselectivities (up to 10:1) along with exclusive control over regio- as well as anti-selectivity are the main features with a good scope of substrates. The method has successfully been applied in the enantioselective syntheses of two biologically important molecules, viz (-)-cytoxazone and L-threo-DOPS (droxidopa). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric bromohydroxylation; Carboxamide; cytoxazone; droxidopa; NaIO4